Avaliação do conforto térmico em conjunto habitacional de interesse social: simulação computacional com o programa Solene Microclima - Natalia Carolina Sousa Nascentes (2017)
Research findings show that thermal discomfort results in energy expenditure for cooling and/or heating, in addition to a decrease in the output of human activities. The thermal performance of buildings is directly linked to thermal comfort and is related to the thermal properties of the materials, shading, and other factors. In order to demand and standardize parameters for construction, the performance standard NBR 15575 came into force in 2013. Among other directions, it lays down the guidelines for thermal performance of multiple-floor residential buildings. Due to public works and geological risks, housing complexes are being implemented in Belo Horizonte in order to replace occupations. They integrate the urban fabric on account of their number and the space they occupy. The aim of this work was to evaluate the microclimate generated in a social-interest housing complex and to investigate alternatives to improve the internal thermal comfort of residential units, as well as of their external common areas. The methodology adopted was based on a computer simulation, analysing the current situation and scenarios that take into consideration aspects such as the influence of vegetation, tree shading, and the albedo of surface of facades. The programme used to create the simulations was Solene Microclima, which was developed by the CRENAU laboratory (France) and validated through field measurements and statistical tests. The results obtained from the simulations were compared to internal and external thermal comfort indexes based on the variables in the simulated answers, such as air temperature and humidity, radiant temperature, and wind speed. It was observed that vegetation scenarios and albedo changes affected the results of internal and external thermal comfort in the housing complex, particularly when there where shading areas receiving direct solar radiation. However, there was a limitation regarding the proposed positioning of vegetation, as well as the choice of species, due to the restrict space between the buildings. Therefore, the importance of vegetation as a strategy for comfort and improvement of thermal performance of buildings should be considered still at the project phase.